2005
DOI: 10.1002/cphc.200400417
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Response Analysis and Power Generation by Single‐Cell Stretching

Abstract: To harvest useful information about cell response due to mechanical perturbations under physiological conditions, a cantilever-based technique was designed, which allowed precise application of arbitrary forces or deformation histories on a single cell in vitro. Essential requirements for these investigations are a mechanism for applying an automated cell force and an induced-deformation detection system based on fiber-optical force sensing and closed loop control. The required mechanical stability of the setu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 46 publications
2
67
0
Order By: Relevance
“…Cells are assumed to exert a contractile force of magnitude F m when they are stretched beyond a critical strain ϵ crit , whereas the contractile force is zero below this stretching threshold. Such an active contractile response as a response to stretching is consistent with experimental findings for individual cells (23). Mathematically, such a response is represented by a Heaviside step function,…”
Section: Discussionsupporting
confidence: 85%
“…Cells are assumed to exert a contractile force of magnitude F m when they are stretched beyond a critical strain ϵ crit , whereas the contractile force is zero below this stretching threshold. Such an active contractile response as a response to stretching is consistent with experimental findings for individual cells (23). Mathematically, such a response is represented by a Heaviside step function,…”
Section: Discussionsupporting
confidence: 85%
“…Because this passive strengthening and ab initio formation of domains under force occurs on time scales that are considerably faster than the active cytoskeletal response, we see it as a strong candidate for the elusive force-sensor (3)(4)(5)(6)(7)(8), which triggers the activation of signaling pathways leading to force-dependent regulation of adhesion in living cells. This passive sensing requires only an intact cell membrane with mobile adhesion proteins and should be noticeable even before proper focal adhesions or stress-fibers are formed, which indeed seems to be the case, not only in the motile cells capable of rapid adhesion and translation (36) but also in focal-adhesion forming cells (4).…”
Section: Statistical Elastic Theory and Discussionmentioning
confidence: 99%
“…Under force, the adhesion domains grow (3) (a phenomenon called mechanoresponse, which is also related to mechanosensing, the ability of cells to sense and respond to rigidity) presumably by applying internal forces that interrogate the substrate (4). Forceinduced strengthening is concomitant with the stiffening of the cytoskeleton (3,5,6), leading to the widespread belief that active regulation of the cytoskeleton is solely responsible for mechanoresponse (3,(5)(6)(7)(8)(9). However, this actively driven cytoskeletal remodeling due to external mechanical stimulus is expected to occur over time scales of minutes (4).…”
mentioning
confidence: 99%
“…Since the early 1980s, several techniques have been developed to characterize the forces generated by living cells (3)(4)(5) and to investigate the effect of the mechanical properties of twodimensional (2D) substrates (6)(7)(8). It was shown that cells are able to sense and respond to the rigidity of their surroundings.…”
mentioning
confidence: 99%